PSIKOLOGI KEPRIBADIAN HUMANISTIK TOKOH DORY DALAM FILM “FINDING DORY” - Dhea Sophia Ananda (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This study focuses on analyzing the Hierarchy of Needs by the main character named Dory of the animated film titled Finding Dory which was produced by Pixar Animation Studios in 2016. This study aims to examine the elements of the hierarchy of needs applied by the main character named Dory by using Abraham Maslow's theory. The qualitative descriptive method is applied in this study. This study used the observation technique as data collection technique to carefully collect the needed data. Research data is presented in written form collected from dialogues and digital film scripts. The results of the study found that there are five stages of Hirearchy Needs manifested by the main character of Finding Dory such as: psychological needs, safety needs, belonginess and love needs, esteem needs and self-actualization needs.